The Influence Of Ewom By Beauty Blogger Tasya Farasya And Product Quality On The Decision To Purchase Somethinc Cushion - Mutiara Azahra; Puji Isyanto; Neni Sumarni (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This study aims to analyze the impact of electronic word-of-mouth (EWOM) by beauty bloggers on purchasing decisions for Somethinc cushion products, as well as to examine the influence of product quality on these purchasing decisions. Research method—The research employed descriptive and verification methods, utilizing multiple linear regression analysis. A sample of 96 consumers who use Somethinc cushion products was analyzed, following Hair's formula. Result— The findings indicate that the EWOM variable from beauty bloggers has a positive and significant influence on the decision to purchase Somethinc Cushion products. Additionally, product quality also shows a positive and very significant impact on purchasing decisions. Conclusion— Consumers continue to seek information from beauty bloggers when making purchasing decisions, highlighting the importance of EWOM and product quality in the cosmetics market.